Analisis Dampak Kebijakan Keringanan Biaya Penyambungan Tambah Daya Terhadap Adopsi Pelanggan dan Kelayakan Bisnis PLN - Tommy Tommy; Iwa Garniwa (Pusat Riset dan Inovasi Nasional, 2026)
In conducting its business and fulfilling its role in providing reliable energy, PLN is inevitably involved in sales and purchase transactions, which naturally involve sellers and buyers. PLN sells electricity to all sectors, including the government, industry, offices, and even households. A healthy company is one that has a smooth cash flow. With a smooth cash flow, the company will be able to grow by reinvesting its existing funds and ultimately increase its business capital and profits in the future. It is noted that in the case of strategic customer arrears, especially customers with special classification codes in 2020, the amount of arrears was the highest in the last 5 years, totaling Rp. 717,678,961,659. This is further exacerbated by the conditions in the field, where the installed power in each customer plot is still small, while the actual usage in the field is higher. PLN needs to review, strategize, and make decisions on the events in the field. By introducing a Connection Fee Reduction Policy for Additional Power, which aims to encourage customers to increase their power so that the number of kWh per month that can be claimed or calculated can increase PLN's revenue. From these calculations, a payback period of approximately 7.3 months and an IRR of 163% were obtained on the opportunity loss from the total BP of Rp 32.7 billion, with additional revenue from kWh usage of Rp 5.1 billion per month.